Raising Keynes: A General Theory for the 21st century - Stephen A. Marglin (EconomiA, 2018)
Keynes's General Theory argues there is no self-regulating mechanism that guarantees full employment. Keynes's vision has been distorted by mainstream Keynesians to mean that it is the warts on the body of capitalism, not capitalism itself, that are the problem: frictions and imperfections and rigidities may interfere with the mechanism for self-regulation that inheres in the perfectly competitive model. This distortion has two supposed corollaries, first, that the more the economy resembles the textbook model of perfect competition, the less likely are lapses from full employment; second, that since imperfections are limited to the short run, so are lapses from full employment. Keynes was unable to convince the economics profession that the problem is capitalism; that the warts, real though they are, obscure a more fundamental problem. The reason is that Keynes lacked the mathematical tools to substantiate his vision. This paper deploys tools that were unavailable to Keynes, in order to lay the foundations of a Keynesian macroeconomics for the 21st century.
Keywords: 330; Keynes; Dynamic vs static models; Flexprice adjustment; Fixprice adjustment